Republic of Poland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1999)
This Selected Issues paper on Poland analyzes tax reform in the country. It highlights that in common with many countries, Poland's personal income tax is based on a definition of global personal income, though some income sources (such as dividends and interest income) are taxed under separate schedules. In addition, agriculture, forestry, and inheritances are taxed under separate laws. The paper presents a medium-term perspective for capital flows to Poland. It highlights that Poland has developed a reputation for sound macroeconomic policies and openness both to trade and financial flows.